Wileńskie miejsca Adama Mickiewicza utrwalone we współczesnych przewodnikach po Mieście wieszczów. (Refleksje językoznawcy-filologa) = Vilnius places of Adam Mickiewicz preserved in current travel guides to the City of the Three Bards. (Reflections of the linguist-philologist) - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Vilnius University, addresses of subsequent residences, the names of meeting places, address of a masonic lodge, names of the houses in which Vilnius social life flourished, addresses of Józef Zawadzki's publishing house, Grand Theater on Trak? Street, Basilian Monastery, Konrad Room, professor Jundziłł's Botanical Garden, garden with osteria "Chiny", eatery "Tivoli", Belmont - mountain of the Philarets, Gate of Dawn, Vilnius Cathedral, Church of St. Johns, interwar Mickiewicz Street? - all these places related to the author of Sir Thaddeus became the reason for linguistic philological reflections defending the thesis that Vilnius is the City of Mickiewicz, who spent one of the most interesting periods of his life there. The Vilnius names excerpted from current travel guides to the City of Romantics and interpreted in accordance with the rules of erudite linguistics not only save Mickiewicz's places from consigning to oblivion, but also permit to reconstruct Vilnius topography.
Keywords: Mickiewicz, Adam (1798-1855); Wilno; miejsce; językoznawstwo erudycyjne; Vilnius; place; erudite linguistics